2013
DOI: 10.1158/0008-5472.can-12-3180
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Inhibits Pancreatic Cancer Desmoplasia by Regulating Stellate Cells

Abstract: Pancreatic stellate cells (PSC), which are implicated in desmoplasia in pancreatic cancer, enhance the malignancy of cancer cells and confer resistance to established treatments. We investigated whether the antifibrotic agent pirfenidone can suppress desmoplasia and exert antitumor effects against pancreatic cancer. Primary PSCs were established from pancreatic cancer tissue obtained during surgery. In vitro, pirfenidone inhibited the proliferation, invasiveness, and migration of PSCs in a dose-dependent manne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 35 publications
7
152
0
Order By: Relevance
“…In addition, pirfenidone has been reported to suppress the differentiation of nasal polyp-derived fibroblasts (25), retinal pigment epithelial cells (26,27) and cardiac fibroblasts (28). Kozono et al (29) reported that pirfenidone-treated pancreatic stellate cells suppressed the invasiveness and migration of pancreatic cancer cells. Pirfenidone's ability to induce EMT reversion in cancer cells may be similar to the previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pirfenidone has been reported to suppress the differentiation of nasal polyp-derived fibroblasts (25), retinal pigment epithelial cells (26,27) and cardiac fibroblasts (28). Kozono et al (29) reported that pirfenidone-treated pancreatic stellate cells suppressed the invasiveness and migration of pancreatic cancer cells. Pirfenidone's ability to induce EMT reversion in cancer cells may be similar to the previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreata and livers were harvested at day 51 in the "early trial" and at day 110 in the "late trial." The tumor volume was measured using an electronic caliper and calculated using the following formula: π/6 × (L × W × W), where L is the tumor at its longest, and W is the tumor at its shortest (Kozono et al 2013). The incidence of liver metastases was evaluated as described above.…”
Section: Ficlatuzumab Treatmentmentioning
confidence: 99%
“…Western blotting was performed as described previously (28). Antibodies used in this study were as follows: anti-TM4SF1 (sc-103267; Santa Cruz, CA, USA), anti-E-cadherin (no.…”
Section: Matrigel Invasion and Migration Assaysmentioning
confidence: 99%